Long-Term Glycemic Variability Is Associated With Arterial Stiffness in Chinese Adults - Zhang, Yuwen; Wu, Shujing; Li, Mian; Wang, Tiange; Xu, Min; Lu, Jieli; Wang, Shuangyuan; Zhang, Jie; Bi, Yufang; Wang, Weiqing; Ning, Guang; Xu, Yu; et al. (Frontiers in Endocrinology, 2021)
Objective: The aim of the study was to investigate the association between the visit-to-visit variability (VVV) of fasting plasma glucose (FPG) and arterial stiffness in Chinese adults. Methods: We performed a cohort study involving 2002 Chinese adults with no history of myocardial infarction or stroke. All the participants attended three visits (the baseline visit in 2008, the 2nd visit in 2009 and the 3rd visit in 2013). We used four measures to define the VVV of FPG across the three visits: the standard deviation (SD), the coefficient of variation (CV), the average successive variability (ASV) and the variability independent of the mean (VIM). We used brachial-ankle pulse wave velocity (ba-PWV) to measure arterial stiffness at the 2nd and the 3rd visits. Results: Compared with the lowest tertile of all the four measurements of VVV of FPG, significantly increased levels of ba-PWV change, ratio of ba-PWV change and the occurrence of the elevated ba-PWV were found in the highest tertile. The odds ratio (OR) and 95% confidence interval (CI) comparing participants in the highest tertile vs. the lowest tertile of FPG-SD was 1.37 (1.01-1.86) for risks of having elevated ba-PWV, even after adjustment for covariates including the mean FPG. Similar results were found for FPG-CV and FPG-VIM. Conclusion: Greater long-term variability of FPG was associated with an increased risk of arterial stiffness, suggesting that the VVV of FPG could be used for an early detection of subclinical atherosclerosis.